MaCySTe: A virtual testbed for maritime cybersecurity - Giacomo Longo; Alessandro Orlich; Stefano Musante; Alessio Merlo; Enrico Russo (SoftwareX, 2023)
The increasing reliance on technology and automation in the maritime sector has made it more vulnerable to cyberattacks. Cyber threats to ships and offshore platforms can have serious consequences, including accidents leading to loss of life, asset damage, or environmental impact. One primary means of countering these threats is developing and testing countermeasures tailored to the shipboard infrastructures and training the personnel. To this aim, we present MaCySTe, an open-source project that provides a testbed reproducing the network infrastructure and core components of the onboard cyber–physical systems. As it interfaces with ship simulators, it allows for realistic testing and training sessions involving cybersecurity and maritime operators. We expect that MaCySTe will contribute to fostering cybersecurity protection and awareness in this critical sector.